Principles of Respiratory Medicine - Udwadia, F. E. Farokh Erach; Udwadia, Z. F. Zarir F.; Kohli, A. F. Anirudh F.; Shah, K. Khyati (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the principles of respiratory medicine. The prime reason for writing a book on pulmonary medicine is our firm conviction that a description of respiratory diseases occurring in India. This book comprised of 22 sections, which include imaging techniques and imaging of the chest, lung physiology, diagnostic and therapeutic procedure, clinical approach to respiratory disease: symptoms and signs, pulmonary tuberculosis, infectious diseases, antibiotic resistance and its management, HIV and the lung, tropical infections involving the lung, airway disease, lung tumors, interstitial lung diseases and other diffuse lung diseases, pulmonary vascular disorders, principles of critical care, acute respiratory distress syndrome, pulmonary manifestations of systemic diseases, diseases of the pleura, diseases of the mediastinum, occupational and environmental lung diseases, drug-induced lung injuries, trauma and chest wall disorders, sleep-related breathing disorders, which are further divided into 74 chapters. A highlight of the book is the discussion on the threat of pulmonary tuberculosis and its unsolved challenges. The epidemiology, the subtle variation in clinical presentation, and the natural history of respiratory diseases in regional contexts have been clearly emphasized. The edition of this book will continue to be useful to medical registrars, registrars in pulmonary medicine, postgraduate students, medical practitioners, consultants in general medicine, and pulmonologists not only in India and Southeast Asia but also to an extent in Africa and South America.